(untitled) (Economic and Political Thought, 2023)
China under ever growing autocratic rule of Xi Jinping, which has started at the end of 2012, is presenting many new proposals and visions, both on domestic and international scene. This article describe those initiatives, usually less known outside of China, as they are, additionally, hidden in the Chinese cultural code. What is obvious and clear: the old civilization is under rejuvenation and together with it an empire, with its own concepts for itself and the whole world. This phenomenon and visible assertiveness of the leadership in Beijing is changing the global balance of power – with relative decline of the West, starting from the USA, and growing impact of emerging markets and the global South, starting from China, and followed by India. After the COVID-19 pandemic and full-scale Russian aggression in the Ukraine it is a high time to adjust to the new global order, still under creation. The change is so deep that any return to the past is just impossible. However, only time will tell what will be the impact of China’s return to the centre of the global scene.